'I am he as you are he as you are me and we are all together'. (23rd June 2022) - Tvorun-Dunn, Maxim
Abstract : Seeing Henry Jenkins's digital-age concept of transmedia convergence as the late-capitalist assembly of 1960s psychedelic intermedia practices, this article adds to a discussion of pre-digital convergence through an examination of the Beatles' countercultural media production and distribution practices. This research examines how these practices are indicative of their cultural ideologies, and how and why these seemingly countercultural beliefs were vulnerable to (and actively complicit in) the formation of neoliberal movements of the digital age. This work finds the psychedelic values held by members of the Beatles to have shaped their song lyrics, distribution, business model and branding in ways that function effectively similar to Jenkins's notion of 'transmedia storytelling'. The result primes audiences for the consumer practices and subjectivity of the postmodern condition. This is accomplished by dispersing narratives and iconography across Beatles' content such that all texts contribute to an oceanic network while lacking any 'core' texts